Quantum Foundations and Technological Futures: A Critical Analysis of Interpretative Frameworks and Socio-Economic Projections - Hossain, K A; Mia, Mohammad Hannan; Miki, Kensuke; Islam, Naval Architect Saiful (Transactions on Engineering and Computing Sciences, 2026)
The proliferating discourse surrounding quantum mechanics (QM) increasingly bridges foundational physics, technological speculation, and spiritual or philosophical narratives. Yet, the rhetorical strategies and epistemic warrants used to construct these bridges remain critically unexamined. This study performs a critical discourse analysis to identify and evaluate the narrative frameworks used to connect standard interpretations of QM with extra-scientific domains of meaning, particularly spiritual creation narratives. We employ a structured qualitative content analysis of three corpora: (1) popular science texts explicating QM (e.g., Rovelli, Greene), (2) contemporary quantum technology market reports and roadmaps (2018-2025), and (3) exemplary spiritual creation texts. Using a codebook developed from science communication and sociology of expectation frameworks, we analyze rhetorical devices, appeals to authority, and argumentative structures. Our analysis reveals three dominant rhetorical bridging strategies: (1) the "miraculous analogy," leveraging quantum weirdness to legitimize spiritual wonder; (2) the "teleological projection," wherein quantum computing's potential is presented as an inevitable, purpose-driven evolution; and (3) the "selective complementarity," which isolates specific QM concepts (e.g., observer effect) while ignoring their technical context to create false parallels with philosophical idealism. While interdisciplinary dialogue is valuable, our findings demonstrate that current popular discourse often relies on epistemically problematic analogies that risk misunderstanding both science and spirituality. We propose criteria for more rigorous, conceptually sound transdisciplinary engagement.